Effectiveness of Proteins and Supernatants Isolated from Bacillus Thuringiensis-Based Bio-Insecticides Against Termites Macrotermes Gilvus (Isoptera: Termitidae). Issue 1 (August 2021) - Pujiastuti, Y; Riskal, A; Suparman,; Arsi, A; Gunawan, B; Sulistyani, D P
Abstract: Bacillus thuringiensis an entomopathogenic bacteria is widely used as an active bio-insecticide, including to control Macrotermes gilvus termites. The effectiveness of B. thuringiensis as a bio-insecticide can be derived from both its protein and spore activities. For this reason, research was carried out to investigate effectiveness of protein separated from spores in controlling these termites. The study was arranged in a factorial completely randomized design with two factors, namely ten isolates of B. thuringiensis (first factor) and bio-insecticide separation treatment (second factor). Propagation medium was bio-urine enriched with 5% molasses. Bio-insecticide treatment was protein and supernatant of B. thuringiensis . Isolates used were B. thuringiensis isolates indigenous South Sumatera. Results showed no differences effect among B. thuringiensis isolates. The highest spore density in a solution without separation was isolate SMR-04 (11.23 x10 12 spores/ml). Average spore density in supernatant treatment was MSP isolates (6.00 x 10 12 spores/ml). The highest mortality occurred in KJ3P1 isolates on supernatant application. LT50 value was in range of 0.921-1.025 days. To control M. gilvus termites with protein and supernatants caused high mortality and low LT50 value. This suggested B . thurigiensis could be a candidate for biological control agents of M. gilvus in the future.